The Relationship Between The Socio-Economic Environment And Attitudes Towards Physical Education Learning Outcomes. Residents Learn Paket B in Makassar City - Syahruddin, Syahruddin; Hasmyati, Hasmyati; Hakim, Hikmad; Bismar, Ahmad Rum; Manganni, Hikmah (UNIVERSITAS NEGERI MAKASSAR, 2021)
This study aims to determine; The relationship between the socio-economic environment and attitudes towards physical education learning outcomes for residents studying Paket B in Makassar City. This research is a type of correlational research. The population is residents studying Paket B in Barru Regency with a sample of 60 residents studying Paket B using cluster random sampling technique. The data analysis technique used is a correlation at a significant level of 95% or 0.05. Based on these results it can be concluded that; (1) There is a significant relationship between the socio-economic environment on the physical education learning outcomes of residents studying Paket B in Makassar City, it is proven that r0 = 0.585 or P < 0.05, (2) There is a significant relationship between attitudes towards physical education learning outcomes for residents studying Paket B in Makassar City, it is proven that r0 = 0.515 or P < 0.05, and (3) There is a significant relationship between socioeconomic environment and attitudes towards physical education learning outcomes of residents studying Paket B in Makassar City, proven R0 = 0.586 or P < 0.05.